Game Mining: How to Make Money from those about to Play a Game - Wolpert, David; Bono, James (Entangled Political Economy, 2014)
It is well known that a player in a non-cooperative game can benefit by publicly restricting his possible moves before play begins. We show that, more generally, a player may benefit by publicly committing to pay an external party an amount that is contingent on the game’s outcome. We explore what happens when external parties – who we call “game miners” – discover this fact and seek to profit from it by entering an outcome-contingent contract with the players. We analyze various structured bargaining games among such miner(s) and players that determine such an outcome-contingent contract before the start of the original game. These bargaining games include playing the players against one another as in the original game, as well as allowing the players to pay the miner(s) for exclusivity and first-mover advantage. We establish restrictions on the strategic settings in which a game miner can profit and bounds on the game miner’s profit. We also find that game miners can lead to both efficient and inefficient equilibria.